Affron® and increase in positive mood: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (2nd July 2021) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: Following an application from Pharmactive Biotech Products, S.L. submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Spain, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to affron ® and contributes to maintain a healthy mood. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is affron ®, an aqueous saffron extract with a content of the sum of crocins and safranal typically between 3.5% and 3.9%. The Panel notes that affron ® is sufficiently characterised. The claimed effect proposed by the applicant is 'contributes to maintain a healthy mood'. The Panel notes that increase in positive mood is a beneficial physiological effect for individuals with low mood or anxiety. One human intervention study showed that consumption of affron ® at a dose of 28 mg/day for 4 weeks improves mood in a population of adults with low mood. However, the results have not been replicated in other studies. The information supplied by the applicant did not provide evidence for a plausible mechanism by which affron ® could exert the claimed effect. The Panel concludes that the evidence is insufficient to establish a cause and effect relationship between the consumption of affron ® and increase in positive mood.